Effect of Hormonal Priming on Seed Germination and Initial Growth of Cambodian Rice in Salt Stress Condition - Sour, Vannak; Sour, Piseth; Vorn, Young; Sim, Sokrous (MultiTech Publisher, 2024)
This experiment aimed to investigate the effect of hormonal priming with cytokinins and gibberellin on seed germination under salt stress conditions and its subsequent impact on the initial growth of Oryza sativa cv. Phka Rumduol. The experiment was divided into two parts: Part one examined the effect of hormonal priming (cytokinins, gibberellin) on seed germination of rice under salt stress (150mM NaCl solution). This part was arranged in a completely randomized design (CRD), and data collection included seed germination percentages, germination index (GI), and root and shoot length of rice seedlings. Part two investigated the effect of hormonal priming (cytokinins and gibberellin) on seed germination and initial growth of rice seedlings in nursery conditions. Similarly, this part was conducted in a CRD, with data collection spanning 30 days. Parameters assessed included seed germination percentage at 10 days after sowing (DAS), as well as root and shoot length, fresh and dry weight at 10, 20, and 30 DAS. Priming rice seeds with cytokinins and gibberellin induced seed germination under salt stress conditions and promoted rice seedling growth in the nursery compared to the control treatment of distilled water priming only. The overall results indicated that gibberellin at concentrations of 50ppm and 100ppm exhibited the greatest potential for promoting rice seed germination and initial seedling growth.